Cost Distortion and Profitability: Evaluating Activity-Based Costing Systems: Sistem Activity Based Costing: Dampak Distorsi Biaya dan Profitabilitas - Studi Deskriptif Kuantitatif - Moch Rofiq; Santi Rahma Dewi (Academia Open, 2024)
This study aimed to investigate the implementation of Activity Based Costing System (ABC) on cost distortion and profitability in PT. Bina Graha Sejahtera. The research method used was a quantitative descriptive study with field research techniques. The research object was PT. Bina Graha Sejahtera, and the subject was the Cost of Goods Manufactured Report for the year 2019. The results showed that the implementation of ABC resulted in lower cost calculations for Plate Joint Spun Pile 400 mm and 500 mm products, which were Rp. 133,266 and Rp. 160,290, respectively. The profitability level of the company also increased to 8% for both products. The implication of this study is that the implementation of ABC can reduce cost distortion and increase profitability in companies. Highlight : Resume keywords and phrases are specific abilities, skills, expertise, and traits recruiters and hiring managers look for in a candidate. Keyword research can provide insights into current marketing trends and help center content on relevant customer acquisition. Keywords in a manuscript should convey the main topics of the study, highlight the importance of the research, be concise, and attract readers. Keywords: resume keywords, keyword research, manuscript keywords, Python keywords, bullet points.